Histopathology of intestinal villi in neonatal and paediatric age: main features with clinical correlation - Part II - Rossi, Chiara; Simoncelli, Gloria; Arpa, Giovanni; Stracuzzi, Alessandra; Parente, Paola; Fassan, Matteo; Vanoli, Alessandro; Villanacci, Vincenzo (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
In this paper, we will continue the description of histological findings of infantile and paediatric small bowel alterations with the main clinical pictures and differential diagnosis. We emphasise once again the need to evaluate the biopsies in an adequate clinical contest and with a systematic approach, including epithelial alterations, lamina propria changes, mucosal architecture, and the distribution of inflammation, together with other morphological signs more specific of certain diseases. We describe the histological findings of coeliac and Crohn’s disease, gastrointestinal food allergic diseases, Langerhans cell histiocytosis, nutritional deficiencies and infections. Finally, we suggest the principal issues in the drafting the pathological report for appropriate interpretation and usefulness in clinical practice. (read more)